The importance of immunohistochemical methods in diagnostic algorithm at differentiation of benign and malignant processes of breast. - Bondareva V.O. (Морфологія, 2007)
Increasing of morbidity and high death rate among of patients with breast cancer (BC) stipulates a necessity of looking for effective methods of diagnostic and treatment of malignant tumors, and also analysis of the factors, that determine clinical course of disease and its forecast. In our investigation the level of expression of markers spectrum was analyzed, that most often used at conducting of differential diagnostic (DD) of benign and malignant process of breast. This spectrum includes α-SMA, MSA, collagen IV, S-100, fractions of cytokeratins – CK7, CK19, CK of squamous epithelium, pancytokeratins and vimentin for patients with different age, who need in verification of the diagnosis, with the purpose of an estimation of degree of the significance and diagnostic value of the indicated markers. It was obtained, that among 35 cases for the patients with suspicion on BC the diagnosis of a malignant was affirmed in 15 cases (42,8%), whereas among the women with previously benign (80), for 12 of them (15%) was established BC. Also it was established the immunohistochemical profile for the most difficult diagnoctical cases of breast, that not only decides the volume of a surgical intervention, but also promotes definition of the forecast, quality of life and survival rate.